Below-the-knee drug-eluting stents and drug-coated balloons. (January 2012) - Karnabatidis, Dimitris; Spiliopoulos, Stavros; Katsanos, Konstantinos; Siablis, Dimitris
Endovascular procedures have evolved to the mainstream treatment of choice for revascularization of infrapopliteal obstructive disease, especially in patients suffering from critical limb ischemia and multiple comorbidities. However, standard balloon angioplasty is limited by the potential of a suboptimal acute outcome due to elastic recoil and/or flow-limiting dissection, followed by neointimal hyperplasia and progressive vascular restenosis even in the case of bare-metal stent use. Drug-eluting stents and drug-coated balloons are emerging endovascular technologies with the promise of significant inhibition of vessel restenosis and improved clinical outcomes. The current review outlines the drug-eluting properties of those instruments and summarizes the currently available clinical data. The authors critically appraise the current status and also provide a glimpse of the near future of endovascular below-the-knee treatments.